3-Nitrooxypropanol Decreased Enteric Methane Production From Growing Beef Cattle in a Commercial Feedlot: Implications for Sustainable Beef Cattle Production - Alemu, Aklilu W.; Pekrul, Liana K. D.; Shreck, Adam L.; Booker, Calvin W.; McGinn, Sean M.; Kindermann, Maik; Beauchemin, Karen A. (Frontiers in Animal Science, 2021)
Effects of the investigational methane (CH4) inhibitor 3-nitrooxypropanol (3-NOP) on animal performance, health and enteric CH4 production of beef cattle were evaluated in a commercial feedlot. Two concurrent studies were conducted: a large pen study (4,048 cattle, eight pen replicates per experimental group) to measure animal performance and health and a small pen study (a subset of 50 cattle from the large pen study, n = 25 per experimental group) to measure enteric CH4 emissions. Within the study, animals (body weight ± SD, 282 ± 8 kg) were assigned in a completely randomized design to one of two groups: control, fed a backgrounding diet (70% corn or barley silage, 30% steam-flaked barley grain concentrate; dry matter (DM) basis) and 3-NOP, fed the backgrounding diet containing 3-NOP. The treatment group in the large pen study was adapted to 3-NOP (12 ± 3 d) before receiving the final target level of 200 mg/kg of DM, which was fed for 108 ± 8 d. Animals in the small pen CH4 emissions study received a basal diet or a basal diet with 3-NOP, with the dose increased every 28 d: low (150 mg/kg DM; 1.27 g/d), medium (175 mg/kg DM; 2.25 g/d), and high (200 mg/kg DM; 2.75 g/d). Intake in the small pens was monitored by electronic feeding bunks and CH4 was measured using the GreenFeed system. In the large pen study, total weight gained, average daily gain, and animal health variables were not affected by 3-NOP, but DM intake (DMI) tended to decrease (P = 0.06) by 2.6% relative to control (8.07 kg/d), while gain:feed ratio tended to be improved (P = 0.06) by 2.5% relative to control (0.161 kg weight gain/kg DMI). In the small pen study, average daily consumption of 3-NOP increased with inclusion rate whereas average DMI was decreased by 5.4% (P = 0.02) compared with control (10.4 kg/d). On average, addition of 3-NOP decreased (P = 0.001) CH4 emissions (g/d) by 25.7% and yield (g CH4/kg DMI) by 21.7%. In conclusion, supplementing a backgrounding diet with 3-NOP decreased CH4 yield and tended to improve feed efficiency of beef cattle fed in a commercial feedlot with no negative impacts on animal health.